2015
DOI: 10.1016/j.ydbio.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Negative Fgf8-Bmp2 feed-back is regulated by miR-130 during early cardiac specification

Abstract: It is known that secreted proteins from the anterior lateral endoderm, FGF8 and BMP2, are involved in mesodermal cardiac differentiation, which determines the first cardiac field, defined by the expression of the earliest specific cardiac markers Nkx-2.5 and Gata4. However, the molecular mechanisms responsible for early cardiac development still remain unclear. At present, microRNAs represent a novel layer of complexity in the regulatory networks controlling gene expression during cardiovascular development. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 67 publications
(88 reference statements)
1
44
0
Order By: Relevance
“…The authors suggested the miR-130 family could be a promising therapeutic target for invasive bladder cancer. Some other studies revealed miR-130 also participated in cardiac development and pulmonary hypertension2122. So far, rare study focused on miR-130a in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested the miR-130 family could be a promising therapeutic target for invasive bladder cancer. Some other studies revealed miR-130 also participated in cardiac development and pulmonary hypertension2122. So far, rare study focused on miR-130a in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…; Jafarzadeh & Soltani, ), and miR‐140‐5p and miR‐130 modulate BMP2 signalling in embryonic vertebrates (Lopez‐Sanchez et al. ; Gan et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…In developing systems, miRNAs show specific temporal and spatial expression patterns (Ahmed et al 2015), and have been functionally implicated in events requiring cell fate determination. The numerous developmental processes involving an active role of miRNAs include gametogenesis, preimplantation and early embryonic stages, neurogenesis and somitogenesis (Ahmed et al 2015;Lopez-Sanchez et al 2015;Bhattacharya et al 2016). However, the association of developmental defects with miRNA mutations in humans and other mammals is rare (de Pontual et al 2011;Parchem et al 2015;Yang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs (miRs) tend to mediate their effects by inducing RNA degradation. Recent studies defining specific roles of miRs included stimulation of cardiomyocyte proliferation (miR-410 and miR-495) [34], linkage of BMP signaling to regulate early cardiac specification (miR130) [35], and inhibition of epithelial to mesenchymal transition in the avian atrioventricular canal (miRs 23b, 199a, and 15a) [36]. Other studies of miRs have focused on expression patterns in specific disease states, looking at patterns of expression and beginning to correlate these to function.…”
Section: Introductionmentioning
confidence: 99%